Pengaruh Peranan Masyarakat Dalam Perencanaan Pembangunan - Arifianti, Sari Maharani; Lubis, Nabila; Putri, Apriliani Alicia; Harahap, Nurhayati (Melati Institute, 2023)
Because the direction of development is determined through this process, development planning becomes very important. It is the government's responsibility to pay attention to community aspirations in the development planning process because this is very important. The aim of this research is to examine how community involvement influences development planning. The aim of the research is to determine the extent of community involvement in the development planning process and the impact of this involvement on the process itself. Qualitative methodology is used in the research process. The conclusion obtained from research that has been carried out using all the data collected is that community involvement in development planning is very significant, and it can be said that the community is the main goal of development.